2020
DOI: 10.3389/fneur.2020.566895
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomical and Physiological Basis of Clinical Tests of Otolith Function. A Tribute to Yoshio Uchino

Abstract: Otolithic receptors are stimulated by gravitoinertial force (GIF) acting on the otoconia resulting in deflections of the hair bundles of otolithic receptor hair cells. The GIF is the sum of gravitational force and the inertial force due to linear acceleration. The usual clinical and experimental tests of otolith function have used GIFs (roll tilts re gravity or linear accelerations) as test stimuli. However, the opposite polarization of receptors across each otolithic macula is puzzling since a GIF directed ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 108 publications
0
15
0
Order By: Relevance
“…In zebrafish, it was further shown that, while early-born afferent neurons connect hair cells to the Mauthner cell, those occurring later only project to the central nucleus [210]. Modified after [22,37,47,196,211,212].…”
Section: Hair Cells Depend On Eya1 Sox2 and Atoh1mentioning
confidence: 99%
See 1 more Smart Citation
“…In zebrafish, it was further shown that, while early-born afferent neurons connect hair cells to the Mauthner cell, those occurring later only project to the central nucleus [210]. Modified after [22,37,47,196,211,212].…”
Section: Hair Cells Depend On Eya1 Sox2 and Atoh1mentioning
confidence: 99%
“…It appears that a bistable situation then determines of Emx2 in the rostral sibling through Notch-mediated lateral inhibition, which then determines the caudal position for the kinocilium of the rostral sibling and the emergence of the opposing polarity [23]. [22,37,47,196,211,212].…”
Section: Hair Cells Depend On Eya1 Sox2 and Atoh1mentioning
confidence: 99%
“…At present, the relationship between utricle diseases and structural lesions or functional abnormalities is not very clear in the clinic [11]. To deeply understand the working principle of the complex and subtle otoliths and accurately judge the specific causes and locations of abnormal utricle function, it is necessary to understand the detailed perception mechanism of the utricle.…”
Section: Introductionmentioning
confidence: 99%
“…Details of how the vestibular system really works started to be elucidated by Mach (1838–1916) [8], Crum Brown (1838–1922) [9], Breuer (1842–1925) [10], Hőgyes (1847–1906) [11], Ewald (1855–1921) [12], Bárány (1876–1936) [13], Lorente de No (1902–1990) [14], Lowenstein (1906–1999) [15] and others [16]. The journey continues to the present day [17,18]. The first articles we could find in Deutsche Zeitschrift f .…”
Section: Introductionmentioning
confidence: 99%